Essay Test Integrated with Socio-Scientific Project-Based Learning for Scientific Argumentation: Tes Esai Terintegrasi dengan Pembelajaran Berbasis Proyek Sosio-Saintifik untuk Argumentasi Ilmiah - Amelia, Sarah; Wicaksana, Ervan Johan; Mursyd, Danial (Pedagogia : Jurnal Pendidikan, 2025)
Scientific argumentation is a key competency for developing students' logical, critical, and systematic thinking. However, current teaching methods have not effectively fostered this skill. This study aims to evaluate the impact of a learning model that integrates a Problem-Based Learning (PBL) approach focused on Socio-Scientific Issues (SSI) in enhancing students’ scientific argumentation abilities. The research was conducted at SMAN 8 Muaro Jambi during the 2024/2025 academic year, involving 105 grade XI phase F students selected through purposive sampling. Class XI F1 served as the experimental group, while XI F2 was the control group. A quasi-experimental design was applied using an unequal pre-test post-test control group model. Data analysis employed a One-Way ANCOVA test. The results indicate that the SSI-based PBL model had a moderate effect on students’ written scientific argumentation skills, as shown by [F(1,67) = 5.521, p = 0.022, np² = 0.076]. Therefore, it can be concluded that the implementation of SSI-based PBL positively contributes to improving students’ scientific argumentation abilities. Highlights: Emphasizes the role of Problem-Based Learning in improving argumentation skills. Uses Socio-Scientific Issues to engage students in real-world contexts. Demonstrates a moderate positive effect on students’ written scientific arguments. Keywords: Scientific Argumentation, Problem-Based Learning, Socio-Scientific Issues, Quasi-Experimental Design, Critical Thinking